Effects of heat stress on Hsp90a2b and Hsp10 mRNA expression and blood cell apoptosis in rainbow trout Oncorhynchus mykiss (Walbaum, 1972) - Luo, Zhicheng; Zhou, Yanjing; Liu, Zhe; Xia, Binpeng; Wang, Yongjie (Indian Journal of Fisheries, 2019)
To study the response to heat stress in rainbow trout Oncorhynchus mykiss (Walbaum, 1972), the expression of heat shock protein genes Hsp90a2b and Hsp10 in selected tissues and apoptosis of blood cells were investigated at water temperatures of 18, 21, 23, 24, 25 and 26°C. Expressions of Hsp90a2b in the gill, mid-kidney, brain, heart and muscle were generally upregulated with increasing temperature. Hsp90a2b expression in the liver increased rapidly at 21°C and then showed a significant decrease and finally a significant increase at 25°C and 26°C (p<0.05). Hsp10 expression showed an irregular but overall increasing tendency in gill, spleen and mid-kidney and a wave-like increasing pattern in liver, heart and muscle. Levels of Hsp90a2b at 25°C and Hsp10 at 26°C in all tissues were always significantly higher compared to 18°C (p<0.05). The apoptosis rate at 21°C was significantly higher than that at 18°C, followed by a fall and was the highest at 25°C. All these data indicated that the heat shock response already occurred at 21°C which induced expressions of Hsp90a2b and Hsp10 as well as blood cells apoptosis and 25°C may be a key temperature for stress response in rainbow trout.